Developing Content-Based Syllabus for Nursing Students at Politeknik Kesehatan Makassar - K., Baharuddin (State University of Makassar, 2022)
The objective of the research was to design the appropriate content-based syllabus for the nursing students’ need and to identify the suitable and relevant topics to the nurses’ duties in nursing practice for the nursing students at Politeknik Kesehatan Makassar.The research employed descriptive method. The population was the fourth semester students of Nursing Department, English lecturers and nurses at Wahidin Sudirohusodo Hospital Makassar. The total sample of this research was 50 respondents which were selected based on purposive sampling techniques. The researcher took 40 nursing students, 5 English lecturers, and 5 senior nurses who have experienced at the hospital in the foreign countries. The collection of data was done by distributing the questionnaires to the respondents to identify the students’ needs to attend the Nursing Department and their objective or their needs, and also to discover their mastery level on the competencies needed and the main priority of competencies. The data was analyzed by applying descriptive statistics. The findings of the study indicated that the appropriate syllabus for Nursing Students at Politeknik Kesehatan Makassar is the topical syllabus which is organized by the topics or themes. The suitable topics consist of content-subjects, general subjects and suggested subjects.Keywords: Content Based Syllabus, Nursing Students